(untitled) (PHILM. Rivista di filosofia e cinema, 2024)
The article establishes a connection between the aberrant movement of montage as discussed by Gilles Deleuze in his two-volume work on cinema and the concept of assemblage [agencement], as presented by the author in collaboration with Félix Guattari in their published works. Aberrant montage and assemblages are, first and foremost, modes of movement and production that inform the ways in which beings and thoughts emerge and unfold. Furthermore, and most significantly, the temporal dimension of the self as manifested in cinema through the “aberrant” dynamics of montage resonates with Deleuze’s explicit ontological explorations of intensive experience and pure qualities.